Numerical Simulation on the Statics Deformation Study of Composite Cross Arms of Different Materials and Configurations - Mohamad D.; Syamsir A.; Itam Z.; Bakar H.A.; Abas A.; Ng F.C.; Razali M.F.; Seman S.A.H.A. (Institute of Physics Publishing, 2023)
Composite materials; Deformation; Manufacture; bracing; Cross arm; Deformation and stress; Deformation studies; Static loading; static structural; Materials properties